ANALISIS KEPUASAN KERJA, KOMITMEN ORGANISASI DAN STRES KERJA TERHADAP PRODUKTIVITAS PEGAWAI (Studi pada Sekretariat Daerah Kabupaten Bireuen - Aceh) - Azhari, Azhari; Aswadi, Khairul (LPPM-UNIKI, 2026)
This empirical study explored factors that significantly impact work productivity among employees of the Bireuen Regency Regional Secretariat. A quantitative associative method was used to measure the variables, and data analysis employed path model statistics. The results revealed (1) direct and indirect influences of commitment and work stress on employee productivity, amounting to 40.27%, 37.84%, and 49.87%, respectively. (2) Simultaneously, job satisfaction, organizational commitment, and work stress contributed to changes in employee productivity by 70,8%. (3) There was moderate causality between job satisfaction, organizational commitment, and work stress.